2023
DOI: 10.3389/fimmu.2023.1142215
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cuproptosis-associated subtypes and signature genes for diagnosis and risk prediction of Ulcerative colitis based on machine learning

Abstract: BackgroundUlcerative colitis (UC) is a chronic and debilitating inflammatory bowel disease that impairs quality of life. Cuproptosis, a recently discovered form of cell death, has been linked to many inflammatory diseases, including UC. This study aimed to examine the biological and clinical significance of cuproptosis-related genes in UC.MethodsThree gene expression profiles of UC were obtained from the Gene Expression Omnibus (GEO) database to form the combined dataset. Differential analysis was performed ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…Researchers have identified several cuproptosis-related genes (CRGs) that contribute to disease progression, with a primary focus on tumor advancement, which may impact the tumor immune microenvironment and predict the effectiveness of immunotherapy (11)(12)(13)(14). Additionally, studies have indicated that CRG signatures are closely associated with certain inflammation-related conditions, including inflammatory bowel disease (15), ulcerative colitis (16,17), and Alzheimer's disease (18,19). Considering that sepsis is characterized by a systemic inflammatory response, we hypothesize that cuproptosis may play a role in sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have identified several cuproptosis-related genes (CRGs) that contribute to disease progression, with a primary focus on tumor advancement, which may impact the tumor immune microenvironment and predict the effectiveness of immunotherapy (11)(12)(13)(14). Additionally, studies have indicated that CRG signatures are closely associated with certain inflammation-related conditions, including inflammatory bowel disease (15), ulcerative colitis (16,17), and Alzheimer's disease (18,19). Considering that sepsis is characterized by a systemic inflammatory response, we hypothesize that cuproptosis may play a role in sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have identified several cuproptosis-related genes (CRGs) that contribute to disease progression, with a primary focus on tumor advancement, which may impact the tumor immune microenvironment and predict the effectiveness of immunotherapy (11)(12)(13)(14). Additionally, studies have indicated that CRG signatures are closely associated with certain inflammation-related conditions, including inflammatory bowel disease (15), ulcerative colitis (16,17), and Alzheimer's disease (18,19). Considering that sepsis is characterized by a systemic inflammatory response, we hypothesize that cuproptosis may play a role in sepsis.…”
Section: Introductionmentioning
confidence: 99%